An Assessment of Taxation Strategies and Policy Interventions for Nigeria's Informal Economy - Aina, Adeola Temitope (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study examined the challenges and opportunities of taxing Nigeria’s informal sector, which contributes significantly to employment and GDP but remains largely untapped for tax revenue. Through qualitative interviews with 40 tax experts across Lagos, Abuja, and Port Harcourt, the research identified structural, administrative, and socio-cultural barriers to effective taxation, including weak enforcement, low tax morale, and poor record-keeping. The study highlighted the potential of technology-driven solutions, simplified tax regimes, and public awareness campaigns to improve compliance. It also explored the role of policies such as the proposed Nigerian tax bill, the integration of BVN (Bank Verification Number) and NIN (National Identification Number) and removing VAT (Value Added Tax) on essential items in formalizing the sector. Drawing on the best international practices, the study emphasized the need for balanced approaches that support informal businesses while enhancing revenue generation. Key recommendations included leveraging digital tools, fostering trust through transparency, and linking tax compliance to access to public services. The findings underscored the importance of addressing systemic challenges to unlock the informal sector’s potential for Nigeria’s economic growth.